Liposome-assisted enzyme catalysis: toward signal amplification for sensitive split-type electrochemiluminescence immunoassay. Issue 12 (11th May 2021) - Fu, Yi-Zhuo; Liu, Xiang-Mei; Ma, Shu-Hui; Cao, Jun-Tao; Liu, Yan-Ming
Abstract : A liposome-assisted enzyme catalysis signal amplification strategy was developed for ECL immunoassay of PSA in a split-type mode. Abstract : Developing an efficient signal amplification strategy is very important to improve the sensitivity of bioanalysis. In this paper, a liposome-assisted enzyme catalysis signal amplification strategy was developed for electrochemiluminescence (ECL) immunoassay of prostate specific antigen (PSA) in a split-type mode. The sandwich immunoreaction occurred in a 96-well plate, and glucose oxidase (GOx) encapsulated and antibody-modified liposomes were used as labels. The ECL detection was carried out using a rGO-Au NP modified glassy carbon electrode (GCE). The large amount of generated H2 O2, i.e. the coreactant of the luminol system, and the excellent catalytic behavior of rGO-Au NPs greatly boosted the ECL signal, resulting in the signal amplification. The developed ECL immunosensor for detecting PSA achieved a wider linear range from 1.0 × 10 −13 to 1.0 × 10 −8 g mL −1 and a detection limit of 1.7 × 10 −14 g mL −1 . The application of the proposed strategy was demonstrated by analyzing PSA in human serum samples with recoveries from 89.0% to 113.0%, and relative standard deviations (RSDs) were less than 6.6%. This work provides a new horizon to expand the application of liposomes for ECL bioanalysis.